PERBEDAAN NILAI LEUKOSIT PRA- DAN PASCAOPERASI SEBAGAI PREDIKTOR LUARAN FUNGSIONAL PERDARAHAN INTRASEREBRAL SPONTAN - Hanif Gordang Tobing; Bismo Nugroho PPR; Mohamad Saekhu; Setyo Widi Nugroho; Affan Priyambodo; Wismaji Sadewo; Syaiful Ichwan; Renindra Ananda Aman; David Tandian; Samsul Ashari (PERDOSNI, 2019)
DIFFERENCES BETWEEN PRE- AND POST-SURGERY LEUKOCYTE COUNTS AS FUNCTIONAL OUTCOME PREDICTOR IN SPONTANEOUS INTRACEREBRAL HEMORRHAGEABSTRACTIntroduction: Hematoma in spontaneous intra-cerebral hemorrhage (SICH) results inflammation due to secondary brain injury. Leukocyte, an inflammation indicator which is routinely examined, known as an outcome predictor in non- operated SICH. The role of inflammation in operated SICH is still unknown, however, pre- and post-surgery leukocyte counts can be a marker of brain tissue damage (brain injury).Aim: This study investigated the characteristics of leucocyte parameters in operated SICH patients and its correlation to functional outcome based on Glasgow Outcome Scale (GOS).Methods: This was a retrospective cohort study for SICH patients who underwent surgery at Department of Neurosurgery in Dr. Cipto Mangunkusumo National General Hospital from January 2012–March 2017. This study analyzed the association between pre-operative leucocyte level with age, pre-operative GCS, hemorrhage volume, length of hospitalization, and six-month post-operative GOS. The correlation of differences of pre-operative and one-day post- operative leucocyte counts with six-month post-operative GOS and hematoma evacuation percentage were analyzed. The analysis was done using Pearson correlation test, Spearman, Chi-square χ2 test, Fisher exact test, and Anova test.Results: There was a significant correlation between differences of leukocyte counts in pre- and post-surgery with GOS. A higher post-surgery leukocyte difference would lower GOS; there was a significant correlation between the leukocytes counts in pre-operative leucocyte and GCS. A higher pre-operative leukocytes counts would lower the GCS.Discussion: The differences of pre-operative and post-operative leucocyte counts is a functional outcome predictors within 6 months in operated SICH patients.Keywords: Leukocyte, outcome, spontaneous intracerebral hemorrage, surgeryABSTRAKPendahuluan: Hematoma pada perdarahan intraserebral spontan (PISS) menyebabkan inflamasi akibat cedera otak sekunder. Leukosit sebagai indikator inflamasi yang rutin diperiksa, diketahui memiliki peranan sebagai prediktor luaran pada PISS yang tidak dioperasi. Sejauh ini belum diketahui peranan inflamasi pada PISS yang dioperasi, namun kadar leukosit pra- dan pascaoperasi dapat menjadi penanda adanya kerusakan jaringan otak (brain injury).Tujuan: Untuk mengetahui karakteristik parameter leukosit pasien PISS yang dioperasi dan kaitannya dengan luaran fungsional berdasarkan skor Glasgow Outcome Scale (GOS).Metode: Studi kohort retrospektif pada pasien PISS yang dioperasi di Departemen Bedah Saraf RSUPN Dr. Cipto Mangunkusumo periode Januari 2012-Maret 2017. Dilakukan analisis antara nilai leukosit praoperasi dengan usia, GCS praoperasi, volume perdarahan, lama rawat inap, dan skor GOS 6 bulan pascaoperasi. Dilakukan analisis perbedaan nilai leukosit praoperasi dibandingkan hari pertama pascaoperasi dengan skor GOS 6 bulan pascaoperasi dan persentase evakuasi hematoma. Analisis dilakukan menggunakan korelasi Pearson, Spearman, uji Chi-square χ2 test, Uji Fisher exact test, dan Anova.Hasil: Pada uji statistik didapatkan korelasi bermakna antara perbedaan nilai leukosit pascaoperasi dibandingkan praoperasi dengan skor GOS. Semakin tinggi nilai perbedaan leukosit pascaoperasi akan menurunkan skor GOS; didapatkan korelasi bermakna antara leukosit praoperasi dengan GCS praoperasi. Semakin tinggi leukosit praoperasi, semakin rendah GCS.Diskusi: Perbedaan nilai leukosit pascaoperasi dibandingkan praoperasi merupakan prediktor luaran fungsional dalam 6 bulan pada pasien perdarahan intraserebral spontan yang dioperasi.Kata kunci: Leukosit, luaran, operasi, perdarahan intraserebral spontan